KUALITAS PELAYANAN PADA SEKTOR PENANGANAN FAKIR MISKIN DI DINAS SOSIAL KABUPATEN KEDIRI - Curtinawati, Rizki Fillya; Handini, RR. Endang Sri; Hasim, Moh (FISIP UWP, 2025)
Public services are an important aspect to pay attention to because the activities and programs implemented aim to meet the needs of the community related to the public interest. The main focus in measuring the quality of government services is an effort to simplify, speed up, and shorten the bureaucracy, as well as ensure transparency and certainty of services. This research uses a qualitative approach. Zeithaml et al.'s theory (1988) is used to see the quality of service in the sector of handling the poor in the Kediri District Social Service. Based on the results of the research, the quality of service in an effort to increase satisfaction is quite good, but each indicator still has shortcomings that must be improved in supporting the service process in particular, indicators of physical evidence or tangible (in terms of facilities and infrastructure) and sympathy or empathy (in terms of attitudes and behaviors that show attention to complaints that need to be improved) while other indicators such as reliability, responsiveness, and assurance have been implemented quite well. In addition, there needs to be motivation given to employees regarding how important it is to provide the best service for the public as an effort to increase satisfaction.